EspM2 is a RhoA guanine nucleotide exchange factor - Lillington, J; Bulgin, R; Berger, C; Lea, S; Matthews, S; Frankel, G; Garnett, J; Arbeloa, A (Wiley, 2010)
Summary We investigated how the type III secretion system WxxxE effectors EspM2 of enterohaemorrhagic Escherichia coli, which triggers stress fibre formation, and SifA of Salmonella enterica serovar Typhimurium, which is involved in intracellular survival, modulate Rho GTPases. We identified a direct interaction between EspM2 or SifA and nucleotide-free RhoA. Nuclear Magnetic Resonance Spectroscopy revealed that EspM2 has a similar fold to SifA and the guanine nucleotide exchange factor (GEF) effector SopE. EspM2 induced nucleotide exchange in RhoA but not in Rac1 or H-Ras, while SifA induced nucleotide exchange in none of them. Mutating W70 of the WxxxE motif or L118 and I127 residues, which surround the catalytic loop, affected the stability of EspM2. Substitution of Q124, located within the catalytic loop of EspM2, with alanine, greatly attenuated the RhoA GEF activity in vitro and the ability of EspM2 to induce stress fibres upon ectopic expression. These results suggest that binding of SifA to RhoA does not trigger nucleotide exchange while EspM2 is a unique Rho GTPase GEF.